The Effectiveness of Moringa Leaves Extract and Cancunpoint Massage Towards Breast Milk Volume on Breastfeeding Mothers - Nevy Norma Renityas (Journal of Ners and Midwifery, 2018)
Insufficiency of fulfillment ASI as the main reason a mother to stop breastfeeding early, she felt ASI owned did not affect the growth of the baby's weight (Binns, 2002). So to help smooth expenditure done with the breast milk of Moringa leaf extract and acupressure on CanCung point (CV 17). The purpose of this study was to analyze the effectiveness of moringa leaf extract and cancung point massage to increase breast milk volume in breastfeeding mothers. The design of this research is pretest and posttest group design. The population of this research is breastfeeding mother in Sanan Wetan area. The population is 20 people. The sample of this research is breastfeeding mother in Sanan Wetan area as many as 20 people. Sampling in this research use purposive sampling. The treatment in this study using Moringa leaf extract at a dose of 800 mg and a massage at the point cancung. Treatment was done 2x in a day for 1 month.The results showed an increase in points between before and after is 375 points, and there is influence between the consumption of Moringa leaves and massaging at point cancung to the increase in volume of breast milk with p = 0.000. Health workers, especially midwives in order to consider complementary therapies that Moringa leaf extract and massaging at point cancung to increase the volume of milk so that achievement can be increased breastfeeding mothers.